The uses of Computer Vision in Artificial Intelligence to extract information from images (Eurasian Journal of Engineering and Technology, 2022)
Machine learning is made possible by the accessibility and availability of sizable data gathered from the sensors, internet, and Modern technology devices in this field. The main idea of machine learning explains the possibility of a computer improving itself over time. Pattern recognition, computer vision, and other learning processes can be aided by organizing conferences, seminars, and group discussions. Experimentation and realworld applicability, this research in computer visions and the concept of machine learning investigates and analyses, assesses, and forecasts the potential of computer vision machine learning applications. The research has discovered that monitored, unmonitored, and machine learning algorithms with semi- monitored are used in computer vision. Support vector machines, neural networks, and k-means clustering are the most widely used methods